RESPONSE OF DIFFERENT HCV GENOTYPES TO INTERFERON THERAPY IN DIFFERENT AGE GROUPS OF CHRONIC HEPATITIS-C PATIENTS - Iqbal, Sajjad; Rahman, Khalil -Ur-; Sheikh, Munir Ahmad; Arshad, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Although new Pegylated Interferon is available, yet the conventional Interferon with the combination of Ribavirin is still the therapy of choice to treat the Hepatitis C patients. This study was conducted to investigate the response of different HCV genotypes in different age groups of chronic Hepatitis C patients treated with conventional InterferonÎ±-2b (IFNÎ±-2b) plus Ribavirin (RBV). Methods: In this cross sectional observational study a total of 520 Hepatitis C patients infected with different HCV genotypes meeting the study criteria were included from August 2010 to January 2013. End of treatment response (ETR), sustained virological response (SVR) and the association of patient’s age with treatment response were evaluated. ETR and SVR were defined as absence of HCV RNA and normal ALT level at the end of therapy and 12 months after the termination of therapy respectively. Results: Out of 520 cases 388 (74.62%) showed ETR. The SVR was observed in 290 (89.23%) out of 325 ETR responders. ETR was higher in males (76.14%) than females (72.77%) while the SVR was almost same in both sex. The highest ETR was noted in genotype 3 (81.15%). The old patients exhibited lower ETR and SVR than youngers in the present study. Conclusions: The properly managed conventional Interferon therapy was effective for Hepatitis C patients infected with genotype 2 and 3 with age <40 years as compared to those patients infected with genotype-1 and 4 or had age >40 years. Keywords: Chronic Hepatitis C, Interferon plus Ribavirin, ETR, SVR